TRANSFORMASI LITERASI DIGITAL GURU SEKOLAH DASAR MELALUI PEMANFAATAN TEKNOLOGI PEMBELAJARAN: SEBUAH STUDI LITERATUR - Safitri, Mutia; Rahayu, Rusnai; Nurazani, Adilah; Nasution, Khoirunnisah; Darwin, Nurul Asikin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The rapid development of technology requires elementary school teachers to possess high levels of digital literacy in order to adapt to the changes in 21st-century learning systems. However, many teachers, particularly at the elementary school level, still face challenges in optimally integrating technology into instructional activities. This study aims to examine various forms of utilizing learning technology to enhance elementary school teachers’ digital literacy and to analyze effective strategies for strengthening these competencies. The method employed is a literature review that examines scientific articles, academic journals, and previous research relevant to digital literacy and educational technology. The findings indicate that the use of digital-based technologies, such as online learning platforms, collaborative applications, and interactive media, can improve elementary school teachers’ technical, cognitive, and social competencies. This study emphasizes the importance of continuous professional development for teachers, institutional support, and educational policies that are responsive to technological advancements in order to support the transformation of teachers’ digital literacy. ABSTRAK Perkembangan teknologi yang semakin pesat menuntut guru sekolah dasar untuk memiliki kemampuan literasi digital yang tinggi agar mampu menyesuaikan diri dengan perubahan sistem pembelajaran abad ke-21. Namun, masih banyak guru khususnya guru sekolah dasar yang mengalami kendala dalam mengintegrasikan teknologi ke dalam kegiatan pembelajaran secara optimal. Penelitian ini bertujuan untuk mengkaji berbagai bentuk pemanfaatan teknologi pembelajaran dalam meningkatkan literasi digital guru sekolah dasar serta menganalisis strategi yang efektif untuk memperkuat kompetensi tersebut. Metode yang digunakan adalah studi literatur dengan menelaah berbagai artikel ilmiah, jurnal, dan hasil penelitian sebelumnya yang relevan dengan tema literasi digital dan teknologi pendidikan. Hasil kajian menunjukkan bahwa penggunaan teknologi berbasis digital, seperti platform pembelajaran daring, aplikasi kolaboratif, dan media interaktif, mampu meningkatkan kemampuan guru sekolah dasar dalam aspek teknis, kognitif, dan sosial. Penelitian ini menekankan pentingnya pelatihan berkelanjutan bagi guru, dukungan institusional, serta kebijakan pendidikan yang responsif terhadap perkembangan teknologi agar transformasi literasi digital guru sekolah.